An assessment of Turkish Airlines: geographical location, fleet mix & international network - Uyan, Berkcan; Ellis, Darren; Pagliari, Romano (Elsevier, 2022)
Istanbul-based Turkish Airlines (THY) is a major global carrier serving more international destinations than any other airline in the world, mostly from its new airport hub (IST). This paper aims to unpack and better understand this achievement by focusing on the airline's geographical location, fleet mix and international network scope. Although a range of other key metrics and/or factors could also generate valuable insights about THY, these three are particularly salient when it comes to explaining the number of international destinations it serves. Geopolitics would be a strong contender for inclusion here as well, although core competitors in the Gulf region and elsewhere share similar international relations, therefore, minimising the key insights available in this regard. The paper adopts a single case study approach whereby a deeper level assessment is made of the airline, including how these three core focal areas contribute to its global reach. Located at the point where Europe and Asia meet, Türkiye is home to over 80 million people, and has a significant domestic air market along with a thriving tourism industry. Operating a sizeable mixed fleet of narrow-body and wide-body aircraft, THY is able to capitalise on its home-base proximity to Europe, and its strong links further afield to North America and elsewhere, to create an extensive global network. Future potential growth exists into currently unserved air markets such as Australia (and the Southwest Pacific more widely), along with the expansion of its existing network in terms of capacity and frequency levels.
Keywords: Turkish Airlines; geographical location; fleet mix; network scope